Insight into differentiation in alkalic systems: Nephelinite-carbonate-water experiments aimed at Ol Doinyo Lengai carbonatite genesis - Lundstrom, Craig C.; Hervig, Rick; Fischer, Tobias P.; Sivaguru, Mayandi; Yin, Leilei; Zhou, Zhenhao; Lin, Xiaobao; Grossi-Diniz, Rodrigo (Frontiers in Earth Science, 2022)
Ol Doinyo Lengai (ODL, Tanzania, East African Rift) is the only known volcano currently erupting carbonatite on Earth with 30 yr. cycles alternating between quiescent carbonatite effusion and explosive, compositionally-zoned silicate eruptions. We performed isothermal crystallization and thermal gradient experiments involving ODL nephelinite, Na2CO3 and H2O to understand magmatic differentiation in this system using SEM-EDS x-ray analysis, x-ray tomography, SIMS and LA-ICPMS to characterize samples. Isothermal crystallization experiments document that hydrous liquids coexist with nepheline+feldspar; as peralkalinity increases, temperatures decrease. Presence of Na2CO3 increases the solubility of water in the liquid. Experiments placing nephelinite with H2O- Na2CO3 in a 1000-350°C thermal gradient show that rapid reaction occurs, resulting in virtually melt-free mineral aggregates having mineral layering reflecting systematic differentiation throughout the capsule. Both types of experiments argue that a continuous interconnected melt exists over a large temperature range in alkalic magmatic systems allowing for differentiation in a reactive mush zone process. Liquid compositions change from carbonate-water bearing nephelinites at high temperature down to hydrous carbonate silicate liquids at <400°C. We propose a model for ODL eruption behavior: 1) nephelinite magmas pond and build a sill complex downward with time; 2) hydrous carbonate melts form in the mush and buoyantly rise, ultimately erupting as natrocarbonatites observed; 3) H2O contents build up in melt at the bottom of the sill complex, eventually leading to water vapor saturation and explosive silicate eruptions. The model accounts for eruption cycling and the unusual compositional zoning of ODL silicate tephras.